2004
DOI: 10.1111/j.1365-2648.2004.03202.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient approaches to clinical conversations in the palliative care setting

Abstract: Palliative care patients often adopt passive roles and tend not to engage in important decision-making, for various reasons. Professionals need to be made aware of this, and should facilitate an open, trusting relationship with patients in order to ensure that important information passes freely in both directions. Professionals should learn to prioritize patient participation and negotiation in their work. With further research, it should be possible to identify the factors that will allow patients to take a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
56
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 16 publications
0
56
0
1
Order By: Relevance
“…32,33 As the number of patients with a wish for hastened death was rather small, theoretical sampling was not possible. These problems were reported in a palliative care context by Sharf et al 34 and Clover et al 35 as well. They even had to stop patient recruitment because of time constraints and missing available resources.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…32,33 As the number of patients with a wish for hastened death was rather small, theoretical sampling was not possible. These problems were reported in a palliative care context by Sharf et al 34 and Clover et al 35 as well. They even had to stop patient recruitment because of time constraints and missing available resources.…”
Section: Discussionmentioning
confidence: 86%
“…They were aware of questionable data saturation 34 or reported that ''convenience sampling was used rather than theoretical sampling as it was necessary to be resourceful and interview available participants.'' 35 These strategies are in contrast to the default use of theoretical sampling, which is recommended in GT. According to the risk of limited validity of data, other researcher in palliative care tried to give rise to more abstract generalizations and trustworthiness of results in case of low recruitment rates by triangulating patients' interviews with professionals' or family members' perspectives.…”
Section: Discussionmentioning
confidence: 98%
“…27 Curtis and colleagues 28 found three discussion areas in need of improvement: prognosis, death, and spiritual issues. While patients may want prognostic information soon after diagnosis, they may not want to raise the issue themselves, 29 placing an emphasis on the willingness of the health professional to initiate the discussion. 30 Lofmark and Nilstun 31 found seriously ill patients valued frank discussions about forgoing life support, even within short clinical encounters.…”
Section: The End-of-life Discussionmentioning
confidence: 98%
“…This relationship appears to involve a power component, with patients expecting providers to be competent, provide consistent caring, and be all-knowing. 25,29 Patients may wish to avoid confrontation with nurses over decision making, due to the uncertainty of their situation and fear of repercussions that may arise from challenging an expert. 29 The balance between honesty and hope when communicating with patients was a common theme: two studies found this was important for good end-of-life communication.…”
mentioning
confidence: 99%
See 1 more Smart Citation